THE LOGICAL FUNCTION IS SIMATE-MATE (THE NOURNING TRADITION OF KARONESE’S CULTURE) - Yohana Ginting; Rahmah Rahmah (State University of Medan, 2014)
ABSTRACT This thesis deals with logical function used in “Simate-mate” (The Mourning Tradition of Karonese’s Culture). The objectives of the study are to find out the types of logical function, describe the social value, and find out the implication of this mourning tradition of Karonese. The research is conducted by a qualitative descriptive approach, which makes a description of the situation or event/occurrence. The data of this study is about the utterances that used in this mourning tradition. The research findings indicate that they were five types of logical function which obtained from the analysis of each data. They were elaboration 10 (8,13%), extension 18 (14,63%), enhancement 59 (47,96%), locution 30 (24,39%), and idea 6 (6,50%). The content of social values in the mourning tradition of karonese’s culture has function to motivate, advice, amuse, and strengthen the condolences family. They had some aspects of communication and have context of implication namely, emotional expression, aesthetical, and educational function that can be as the reflection for the people about the importance of this tradition for the readers especially young generation. Keyword : Functional Grammar, Logical Function, Sociolinguistics.